Increasing water-use efficiency mediates effects of atmospheric carbon, sulfur, and nitrogen on growth variability of central European conifers - Treml, Václav; Tumajer, Jan; Jandová, Kateřina; Oulehle, Filip; Rydval, Miloš; Čada, Vojtěch; Treydte, Kerstin; Mašek, Jiří; Vondrovicová, Lenka; Lhotáková, Zuzana; Svoboda, Miroslav (The Science of the total environment, 2022)
Climate controls forest biomass production through direct effects on cambial activity and indirectly through interactions with CO2, air pollution, and nutrient availability. The atmospheric concentration of CO2, sulfur and nitrogen deposition can also exert a significant indirect control on wood formation since these factors influence the stomatal regulation of transpiration and carbon uptake, that is, intrinsic water use efficiency (iWUE). Here we provide 120-year long tree-ring time series of iWUE, stem growth, climatic and combined sulfur and nitrogen (SN) deposition trends for two common tree species, Pinus sylvestris (PISY) and Picea abies (PCAB), at their lower and upper distribution margins in Central Europe. The main goals were to explain iWUE trends using theoretical scenarios including climatic and SN deposition data, and to assess the contribution of climate and iWUE to the observed growth trends. Our results showed that after a notable increase in iWUE between the 1950s and 1980s, this positive trend subsequently slowed down. The substantial rise of iWUE since the 1950s resulted from a combination of an accelerated increase in atmospheric CO2 concentrations (Ca) and a stable level of leaf intercellular CO2 (Ci). The offset of observed iWUE values above the trajectory of a constant Ci/Ca scenario was explained by trends in SN deposition (all sites) together with the variation of drought conditions (low-elevation sites only). Increasing iWUE over the 20th and 21st centuries improved tree growth at low-elevation drought-sensitive sites. In contrast, at high-elevation PCAB sites, growth was mainly stimulated by recent warming. We propose that SN pollution should be considered in order to explain the steep increase in iWUE of conifers in the 20th century throughout Central Europe and other regions with a significant SN deposition history.
Keywords: stromy; Climatic limitation; Growth trends; Pinus; Nitrogen; cévnaté rostliny; voda; uhlík; Trees; Sulfur; borovice; Drought; Scots pine; Carbon Dioxide; Atmospheric pollution; Carbon; Carbon stable isotopes; dusík; oxid uhličitý; síra; Water; Norway spruce; Tracheophyta